Problem Solving Patologi Sosial Dalam Perspektif Islam - Badi'ah, Siti (AL-ADYAN, 2018)
The development of science and technology, the minimum of employment and the decline in the level of education are very influential on the emergence of social problems in society. Social problems in the community are often referred to as "social pathology." Community disease is the behavior of members of the community which can lead to unrest and insecurity in people's lives. Community diseases in the social community today are increasingly prevalent in the community, especially the local government and very disturbing people who live in the area. Examples of community diseases are gambling, fighting or brawls, drug or drug abuse, alcoholism or drunkenness, prostitution, corruption, and many more public diseases that occur in society today. social is one of the problems that is considered by Islam, various kinds of problems have been explained in the Qur'an to solve this problem, for example giving punishment to people for theft, drunkenness, killing, etc. is a reward for people who do something mass ah which is contrary to Islamic law. This research is an attempt to look at the problem of community diseases in the eyes of the Qur'an. This study has three focus problems, namely: first; efforts to see the type of society's illness in the view of the Qur'an, second; see things that are the background to the emergence of social pathology, and third; efforts to find solutions / knowledge of social pathology in the view of the Qur'an.